Aortic Geometric Alteration Associated With Acute Type B Aortic Dissection: Angulation, Tortuosity, and Arch Type - Sun, Likun; Li, Jiehua; Wang, Lunchang; Li, Quanming; He, Hao; Li, Xin; Li, Ming; Wang, Tun; Zhao, Chenglei; Zhang, Xiaolong; Shu, Chang (Frontiers in Physiology, 2021)
Background: Acute type B aortic dissection is a highly serious aortic pathology. Aortic geometric parameters may be useful variables related to the occurrence of acute type B aortic dissection (aTBAD). The aim of the study is to delineate the alteration in aortic geometric parameters and analyze the specific geometric factors associated with aTBAD. Methods: The propensity score matching method was applied to control confounding factors. The aortic diameter, length, angulation, tortuosity, and type of aortic arch of the aTBAD and control group were retrospectively analyzed via three-dimensional computed tomography imaging created by the 3mensio software (version 10.0, Maastricht, The Netherlands). The geometric variables of true lumen and false lumen in the descending aorta were measured to estimate the severity of aortic dissection. Multivariable logistic regression models were used to investigate the significant and specific factors associated with aTBAD occurrence. The area under the receiver operating characteristic curve (AUC) was used to estimate the performance of the model. Results: After propensity score matching, 168 matched pairs of patients were selected. The ascending aorta and aortic arch diameters were dilated, and the ascending aorta and total aorta lengths were elongated in aTBAD group significantly (P < 0.001). The ascending aorta and aortic arch angulations in the aTBAD group were sharper than those of the controls (P = 0.01, P < 0.001, respectively). The aortic arch and total aorta tortuosities were significantly higher in the aTBAD group (P = 0.001, P < 0.001, respectively). There were more type III arch patients in the aTBAD group than the controls (67.9 vs. 22.6%). The true lumen angulation was sharper than that in the false lumen (P < 0.01). The true lumen tortuosity was significantly lower than that in the false lumen (P < 0.001). The multivariable models identified that aortic arch angulation, tortuosity, and type III arch were independent and specific geometric factors associated with aTBAD occurrence. The AUC of the multivariable models 1, 2, 3 were 0.945, 0.953, and 0.96, respectively. Conclusions: The sharper angulation and higher tortuosity of aortic arch and type III arch were the geometric factors associated with aTBAD in addition to the ascending aorta elongation and aortic arch dilation. The angulation and tortuosity of the true and false lumens may carry significant clinical implications for the treatment and prognosis of aTBAD.